Territory, Jus ad Bellum: The Status of the Golan Heights in Light of the 2024 ICJ Advisory Opinion - علی مسعودیان; سحر خوشدل (Majallah-i Huqūqī-i Biyn/al-milalī-i)
This article examines the application of Articles 2(4) and 51 of the UN Charter in relation to Israel’s claim of sovereignty over the Golan Heights. Israel has cited historical Jewish rule and invoked “defensive conquest” to justify its position. However, this interpretation misrepresents the non-use of force principle. The article references relevant UN Security Council Resolutions and treaty interpretation rules, emphasizing a strict application of international law, which Israel has overlooked. The UN Charter’s main purpose of maintaining international peace supports this strict interpretation. Consequently, the notion of defensive conquest violates Article 2(4) and customary international law. Additionally, the article discusses the 2024 International Court of Justice Advisory Opinion, which reaffirmed the illegality of Israel’s annexation of the Golan Heights and highlighted the prohibition of acquiring territory by force, as established by the UN Charter.